Efficiency and Transparency in Village Fund Budget for Buluh Perindu BUMDes Management at Baru Semerah Village - Satri, Thareq Kemal; Alfisyahri, Nuriah (Universitas Muhammadiyah Yogyakarta, 2023)
This research was conducted to determine the effect of Efficiency and Transparency in the Village Fund Budget on Managing the Village's Economic Potential. This research is quantitative with a descriptive approach. The techniques applied in the data collection process include observation, documentation, and questionnaires. The technique in determining respondents used the Slovin formula with 223 respondents. This research used SmartPLS 3.2.9 software, Partial Least Square systems, and Structural Equation Modeling (PLS/SEM) in data processing procedures to explain the relationship between variables and perform an analysis of a single test. In this study, Village Economic Potential, represented by a Symbol (Y), is the only dependent variable, and Efficiency with a symbol (X1) and Transparency with a Symbol (X2) are two independent variables. The results indicated that efficiency had a positive and significant effect on managing Village Economic Potential because the P-value was less than 0.05 with the original sample value of the Path coefficient of 0.276 or an effect of 27.6% on Village Economic Potential. Transparency also positively and significantly influenced the management of Village Economic Potential because the P-value was less than 0.05 with the original sample value of the Path coefficient of 0.455 or 45.5% on Village Economic Potential.